Indonesia Sistem Monitoring Kesehatan Tanaman Hidroponik Portable di Dalam Ruangan dengan Integrasi Smartphone Berbasis IoT untuk Pertanian Cerdas - Muhammad Rifal Rifdiansyah; Pita Hutabalian; Nadiyah Nur Rafifah; Susilawati, M.Si (Jurnal Ilmiah Wahana Pendidikan, 2026)
Monitoring system based on the Internet of Things (IoT) was developed using an ESP32 microcontroller and the Blynk application. The system integrates temperature and humidity sensors (DHT22), a soil moisture sensor (YL-69), and a light sensor (LDR), transmitting real-time data to a smartphone. The test results indicate that the system accurately and reliably monitors indoor plant conditions. Therefore, this system supports ef icient and water-saving smart farming practices that can be easily implemented by urban farmers and communities.